Engineering and structural solutions for enhancing the stability of reconstructed buildings - KUZMIN, Timur (Ways to Improve Construction Efficiency, 2025)
The engineering and structural stability of reconstructed buildings determines the ability of their load-bearing systems to maintain equilibrium, shape, and functionality under various types of loads. During the reconstruction process, changes occur in the geometry, stiffness characteristics, and working conditions of structures, which necessitates a new approach to design and evaluation of their reliability. The influence of element modernization on the overall stability of the system makes it essential to analyze the stress–strain state, taking into account the interaction of materials, joints, and supports. A particularly important role is played by the combination of analytical and numerical calculation methods, which ensure precise identification of zones of critical stresses, deformations, and loss of equilibrium. The finite element method makes it possible to model complex spatial systems, including defects, openings, and strengthening zones. Analytical approaches – Hooke’s law, equilibrium equations, and Euler’s formulas – make it possible to assess the strength reserve and critical stability parameters for individual elements. This combination of methods forms the basis for a comprehensive assessment of the effectiveness of reconstruction measures. One of the key directions for improving stability is the strengthening of load-bearing elements. The use of steel reinforcement, jacketing, and composite materials allows for a significant increase in the load-bearing capacity of structures without dismantling or excessive increase in the building’s weight. Composites, such as carbon and basalt fibers, are characterized by high strength, low weight, and corrosion resistance, which ensures the durability of reconstructed structures. The application of such materials is particularly effective for historical or socially significant buildings, where minimal intervention in the existing structure is a critical requirement. The efficiency of different strengthening methods is evaluated through specific performance indicators – the ratio between the increase in load-bearing capacity and the cost. Comparative analysis confirms that composite systems demonstrate the highest technical results with long-term economic advantages. The combination of steel reinforcement with composite strengthening provides a balanced solution with optimal parameters of stability, cost, and technological complexity.